2007
DOI: 10.1002/chin.200718004
|View full text |Cite
|
Sign up to set email alerts
|

Approaching Actinide(+III) Hydration from First Principles

Abstract: Theory C 1000 Approaching Actinide(+III) Hydration from First Principles -[hydration energies of [M(OH 2 ) n ] 3+ with M: Ac-Lr and n = 7, 8, 9]. -(WIEBKE, J.; MORITZ, A.; CAO, X.; DOLG*, M.; Phys. Chem. Chem. Phys. 9 (2007) 4, 459-465; Inst. Theor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 1 publication
2
26
1
Order By: Relevance
“…[72,73] 9 ] 3þ clusters are also presented in Figure 5. In the case of [79] and hence gives the confidence in using the present solvation energy methodology.…”
Section: Free Energy Of Extraction Using Thermodynamic Cycle In Solvementioning
confidence: 95%
“…[72,73] 9 ] 3þ clusters are also presented in Figure 5. In the case of [79] and hence gives the confidence in using the present solvation energy methodology.…”
Section: Free Energy Of Extraction Using Thermodynamic Cycle In Solvementioning
confidence: 95%
“…(14) is MoO 2 Cl 2 Á9(±2)H 2 O. Species with hydration numbers of nine or more are thought to occur in aqueous liquid (e.g., Bunyatyan et al, 1974;Hofer et al, 2006;Wiebke et al, 2007), but to our knowledge they have not been reported in the gas phase. We therefore suggest that the apparent dependence on H 2 O may not be due to the formation of a hydrated species, but instead to the formation of increasing amounts of the highly soluble oxychloride at higher total pressure (P H 2 O ).…”
Section: Molybdenum Speciationmentioning
confidence: 97%
“…a Data taken from [124]; b data taken from [123]; c data taken from [125]. (CN = 8,9) [128,129] as well as available experimental data [130][131][132][133][134][135][136] are shown in Table 6.9. In analogy with the Ln III -O the calculated An III -O bond distances are found to decrease almost linearly with respect to the nuclear charge, [142] performed a detailed thermodynamic examination of the selective extraction of Am 3+ from Eu 3+ by two CF − 3 substituted diaryldithiophosphinic acids.…”
Section: Lanthanide(iii) and Actinide(iii) Hydrationmentioning
confidence: 99%
“…a Data taken from [128]; b data taken from [129]; c data taken from [130]; d data taken from [131]; e data taken from [132]; f data taken from [133]; g data taken from [134]; h data taken from [135] and [136]. [129] (see Table 6.10). It can be seen that the single-point corrected LPP MP2 results are about 152 kJ/mol lower than the LPP DFT/BP86 results.…”
mentioning
confidence: 99%
See 1 more Smart Citation